Mauritania : Recent Economic Developments. (IMF Staff Country Reports; Country Report, 1995)
This paper describes economic developments in Mauritania during the 1990s. Significant progress has been achieved in Mauritania since 1992. Economic growth has held up and the rate of inflation has been contained to below 5 percent. The lingering domestic banking crisis was confronted through a comprehensive bank reform. Firm control has been exercised over fiscal and monetary policies, and remedial measures were introduced to cope with unforeseen fiscal outlays for bank restructuring and to counter the impact of a more adverse export environment.